2021
DOI: 10.1038/s41598-021-90388-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium, magnesium, and phosphorus intakes and risk of stroke in Chinese adults

Abstract: Controversial results have been reported about the association of calcium, magnesium, and phosphorus and stroke risk, but none in China. To investigate the association between dietary calcium, magnesium, phosphorus, and stroke incidence in Chinese adults, we collected data from the China Health and Nutrition Survey (CHNS) from 2004 to 2011, including 6411 participants aged 45–79 years and free of stroke at baseline. Diet was assessed by interviews combining 3-d 24-h food recalls and household food inventory we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In Iran, an average intake of phosphate of 1200 mg/day was assessed, and, in another cohort, individuals reported between 180 and 1100 mg of phosphate intake per day [ 6 , 70 ]. Additionally, in a Chinese cohort, a phosphate intake between 700 and 1400 mg/day was assessed [ 114 ]. Taken together, these data and considering the reported underestimation, we can estimate than on average, an adult consumes around 1500 mg of phosphate per day.…”
Section: Dietary Phosphate Intakementioning
confidence: 99%
“…In Iran, an average intake of phosphate of 1200 mg/day was assessed, and, in another cohort, individuals reported between 180 and 1100 mg of phosphate intake per day [ 6 , 70 ]. Additionally, in a Chinese cohort, a phosphate intake between 700 and 1400 mg/day was assessed [ 114 ]. Taken together, these data and considering the reported underestimation, we can estimate than on average, an adult consumes around 1500 mg of phosphate per day.…”
Section: Dietary Phosphate Intakementioning
confidence: 99%
“…Mg is suggested to act in a dose-dependent manner: for each 100 mg/day, the risk is reduced by 2% [65]. However, a recent study in 6411 interviewed participants (aged 45-79 years) free of stroke at baseline suggested that only dietary calcium intake, but not Mg, is associated with a lower risk of stroke in Chinese adults, particularly in men [103]. The observational nature of the studies and lack of RCTs is a limiting factor.…”
Section: Magnesium and Cardiovascular Functionmentioning
confidence: 99%
“…High Mg concentration has been shown in vitro to inhibit the mineralization process and to modulate gene expression of mesenchymal stem cells during osteogenic differentiation. Involvement of Mg transporter SLC41A1 [103] and of Mg substitution for calcium in the hydroxyapatite structure [152] has been suggested.…”
Section: Prospects Of Mg In the Cardiovascular Disease-sarcopenia-osteoporosis Triadmentioning
confidence: 99%
“…Although previous studies [20][21][22][23][24][25][26][27][28][29][30][31][32] have evaluated the relationship between dietary magnesium intake and stroke risk, the results are controversial. A 12-year follow-up study showed that people with a high magnesium diet had a low risk for total stroke.…”
mentioning
confidence: 99%